2019
DOI: 10.1080/03007995.2019.1668204
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and healthcare costs among biologic-naive patients initiating apremilast or biologics for the treatment of psoriatic arthritis: results from a US claims analysis

Abstract: Supplementary Appendix 1. Psoriatic arthritis patient disposition. a Adalimumab, certolizumab, etanercept, infliximab, ixekizumab, secukinumab, or ustekinumab. b Ulcerative colitis, Crohn's disease, rheumatoid arthritis and other inflammatory polyarthropathies (Felty's syndrome), ankylosing spondylitis, and juvenile idiopathic arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
3
12
2
Order By: Relevance
“…Although we observed better persistence and adherence among patients with PsA who initiated the IL-12/23i compared to patients who initiated TNFis and tsDMARDs, a little more than half of patients still discontinued their treatment within 1 year. These findings are similar to other studies conducted over the past several years, in which discontinuation rates within 1 year of treatment initiation ranged from 33% to nearly 70% among PsA patients treated with biologics or other advanced therapies [ 5 , 6 , 8 , 10 , 11 ]. Furthermore, in a study of patients with PsA treated with injectable biologic drugs (adalimumab, certolizumab pegol, etanercept, golimumab, or ustekinumab), the overall discontinuation rate within 2 years of initiation was approximately 80% [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although we observed better persistence and adherence among patients with PsA who initiated the IL-12/23i compared to patients who initiated TNFis and tsDMARDs, a little more than half of patients still discontinued their treatment within 1 year. These findings are similar to other studies conducted over the past several years, in which discontinuation rates within 1 year of treatment initiation ranged from 33% to nearly 70% among PsA patients treated with biologics or other advanced therapies [ 5 , 6 , 8 , 10 , 11 ]. Furthermore, in a study of patients with PsA treated with injectable biologic drugs (adalimumab, certolizumab pegol, etanercept, golimumab, or ustekinumab), the overall discontinuation rate within 2 years of initiation was approximately 80% [ 9 ].…”
Section: Discussionsupporting
confidence: 89%
“…Discontinuation was defined as at least a 60-day continuous gap after fulfillment of days' supply in the previous adalimumab claim. A continuous gap of at least 60 days was chosen on the basis of a review of previous literature evaluating biologic treatment patterns in psoriatic arthritis [15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, greater mean physician encounters were observed for patients indexing to oral immunotherapy in the joint cohort, showed that switching rates were similar among patients initiating oral apremilast versus biologics in those with PSO or PsA. 26,27 Our finding of greater switching within skin and joint and skin cohorts indicates that oral immunotherapy in general might not be as effective and/or tolerated as injectable immunotherapies in the treatment of these chronic conditions because switching medications is considered a potential proxy for lack of treatment effect. 43 Switching was also marginally greater for the joint cohort, although lacked statistical significance.…”
Section: ■■ Discussionmentioning
confidence: 86%
“…Similar results were mirrored in studies comparing apremilast to biologics in patients with PsA and PSO. 26,27 The average 12-month total health care cost for patients with PsA on apremilast was approximately $28,000 versus $37,000 for those on biologics and approximately $21,000 versus $41,000 for patients with PSO. 26,27 Patients who respond well to oral medications may see sufficient treatment effect while incurring considerably lower costs.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation